More Education, Less Volatility? The Effect of Education on Earnings Volatility over the Life Cycle - Judith Delaney; Paul J. Devereux (Institute of Labor Economics (IZA), 2017)
Much evidence suggests that having more education leads to higher earnings in the labor market. However, there is little evidence about whether having more education causes employees to experience lower earnings volatility or shelters them from the adverse effects of recessions. We use a large British administrative panel data set to study the impact of the 1972 increase in compulsory schooling on earnings volatility over the life cycle. Our estimates suggest that men exposed to the law change subsequently had lower earnings variability and less pro-cyclical earnings. However, there is little evidence that education affects earnings volatility of older men.
Keywords: I26; J01; 330; return to education; earnings volatility